A Review on the Product Packaging and Its Influences on Customers (International Journal of Innovative Research in Engineering & Management, 2021)
Many businesses have concentrated on one strategy or another  in order to increase product profit margins. Organizations  have traditionally engaged in this is a processes to increase  number of the customers purchase their goods. Different  technologies are used to assist their goods compete with those  of competitors, and the package type is one of the first steps in  making consumers aware of products. Despite of fact that  packing, also the technique in which consumer evaluates  product's value, has been extensively investigated and the  findings have properly defined the link between packaging  and a customer's buying behavior, the packaging justification  results have effectively defined the relationship between the  packaging and a customer's purchasing behavior. The  majority of a consumer's purchasing decisions are influenced  by packaging and its features. Font type, printed details, wrapping design, and distinctiveness all used as the indicator,  as are colour package, context artwork, and packing content.  Expands & customer lifestyle change, interests in a packaging  as products marketing tactical and trigger for impulsiveness purchases behaviors is expanding. As a consequence,  packaging play critical role that throughout an advertising  relationship, particular at point of a sale, one of the most  influential aspects in customer purchase choices.
Keywords: Behavior; Customer; Packaging; Product; Organization; Purchasing; Quality Impact